Geoecological Mapping to Identify Groundwater Ecosystem Services Conflicts in a Brazilian Municipality - Roque Guerrero, João Vitor; Gomes, Alberto; di Lollo, José Augusto [UNESP]; Lorandi, Reinaldo; Moschini, Luiz Eduardo (Springer Nature, 2021)
This study applies geoecological-based mapping techniques to identify the natural potential of the landscape to promote groundwater ecosystem services. In addition, this diagnosis analyzed its relationship with land use to identify groundwater geoethical conflicts in Brotas municipality, Brazil, which is completely included in the Guarani aquifer system, one of the largest world natural groundwater reservoirs. In the analysis, we used spatial data of geology, soils, land use, terrain forms, DEM and lineament density. The results of land use analysis indicate that the main economical drive force for the study area is the sugarcane production. On the other hand, the analysis shows that local geoenvironmental conditions of this region are favorable to the groundwater production. Finally, the geoethical conflicts chart, produced from the interaction between land use and the potential to provide groundwater ES's chart, showed that 59% of the study area has geoethics groundwater conflicts, i.e., places where anthropic activities endanger the quality and availability of groundwater ecosystem services. The results obtained can support decision making in Guarani aquifer areas for several countries as Brazil, Argentina, Uruguay and Paraguay.
Keywords: Ecosystem services; Geoethics; Groundwater management; Guarani aquifer system